Satu Islam Beda Pemahaman Satu Iman Beda Jalan: Nurcholish Madjid dan Gerakan Pembaruan Pemikiran Islam di Indonesia - Andoni, Yudhi; Qurrata'ayuni Vidhiputri, Shiney (Jurnal Ceteris Paribus, 2025)
This article examines the dynamics of the Islamic renewal movement in Indonesia, with a focus on the thought of Nurcholish Madjid. The research argues that Madjid's thought represents a significant shift from the paradigms of Islamic revivalism and modernism towards neo-modernism, which emphasizes the desacralization of worldly domains and the articulation of Islamic values as a socio-cultural ethic in national life. Using historical research methods with an intellectual history approach, this article analyzes Madjid's controversial 1970 speech, "The Necessity of Renewing Islamic Thought and the Problem of Umma Integration," as a key moment marking a new periodization. The findings indicate that the socio-political context of the transition from the Old Order to the New Order regime catalyzed the birth of Madjid's ideas on "secularization" and "Islam Yes, Partisan Islam No." These ideas aimed to relieve the Muslim community of ideological burdens and reposition Islam's role from striving for state power (politics) to becoming a moral and cultural force in pluralistic Indonesian society. The article concludes that although Madjid's thought sparked polemics, it successfully opened a new discursive space regarding the relationship between Islam and the state. The continuity of his discourse is evident in the emergence of the Liberal Islam Network (Jaringan Islam Liberal/JIL) as a form of liberalization of neo-modernism, which also confirms that the dialectic of "one Islam, different understandings" remains a central characteristic of the history of Islamic thought in Indonesia.